Targeting of the Pilosebaceous Follicle by Liquid Crystal Nanocarriers: In Vitro and In Vivo Effects of the Entrapped Minoxidil - Massimo Fresta; Antonia Mancuso; Maria Chiara Cristiano; Konrad Urbanek; Felisa Cilurzo; Donato Cosco; Michelangelo Iannone; Donatella Paolino (MDPI AG, 2020)
The topical administration of active compounds represents an advantageous strategy to reach the various skin components as well as its appendages. Pilosebaceous follicles are skin appendages originating in the deeper skin layers. They are very difficult to target, and hence higher active dosages are generally required to achieve effective biological responses, thus favoring the rise of side effects. The aim of this work was to design a supramolecular colloidal carrier, i.e., a liquid crystal nanocarrier, for the selective delivery of active compounds into the pilosebaceous follicle. This nanocarrier showed mean sizes of ~80 nm, a good stability, a negative surface charge, and great safety properties. In vitro studies highlighted its ability to contain and release different substances and to successfully permeate the skin. Minoxidil was encapsulated in the nanocarriers and the in vivo biological effect was compared with a conventional dosage form. Minoxidil-loaded liquid crystal nanocarrier was able to selectively reach the pilosebaceous follicle, thus allowing an increased biological effectiveness of the delivered active in terms of biological response, duration of the biological effects, and reduction of collaterals. Our investigation showed that liquid crystal nanocarriers represent a promising device for the treatment of different pilosebaceous follicular impairments/diseases.